Evaluasi Harga Tarif Tol Berdasarkan Analisis Kelayakan Finansial (Studi Kasus: Jalan Tol Medan-Binjai) - Galuh Rahmadyarto; Ari Sandhyavitri; Alfian Malik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Initial tariff rates are generally based on financial calculations so that the initial tariff determination can be more than willingness or ability to pay from potential toll users. Economic analysis used in this research is the cost savings of vehicle operation, and time value saving. While the financial feasibility analysis is NPV, BCR, IRR, payback period and sensitivity analysis to the change of toll rate start. The result of financial analysis with the preliminary toll tariff is Rp 981.00 and the interest rate of 6.78%, these value indicates that the evaluation of the Medan-Binjai toll road tariff is financially feasible. While the sensitivity analysis result on toll tariff states that not all the toll tariff used in Medan-Binjai road tariff is financially feasible. Keywords : evaluation, tariff, highway, vehicle cost operating, finance, sensitivity analysis